Analysis and modelling of the interactive effects of temperature and light on phytoplankton growth and relevance for the spring bloom - Nicklisch, Andreas; Shatwell, Tom; Kohler, Jan (Journal of Plankton Research)
Global climate change alters the relationship between temperature and light in aquatic ecosystems, which is expected to affect the success of different phytoplankton species. To examine this, the interactions between temperature, photoperiod and light exposure (LE) (integral daily light supply) on specific growth rates were analysed for Limnothrix redekei, Planktothrix agardhii (cyanobacteria), Nitzschia acicularis and Stephanodiscus minutulus (diatoms). A model of factor interactions was developed based on new (P. agardhii and St. minutulus) and previously published laboratory studies. It describes the measured data with high precision. Temperature and photoperiod affect the parameters of the light-growth response curve differently, but these effects are the same for all species. The link between functions for temperature and photoperiod is more species-specific. Using meteorological data, the model developed here was used to study the interplay of these factors during a spring bloom in Lake Müggelsee (Berlin). It was found that while all three factors influenced phytoplankton growth, temperature and photoperiod were more important than LE. Both the intensities of the factors and the interactions between them influenced each species to a different degree. The results may help improve our understanding and ability to predict shifts in phytoplankton communities caused by weather patterns and climate change.